Diagnostic accuracies of screening for atrial fibrillation by cardiac nurses versus radiographers - Jes Sanddal Lindholt; Axel Cosmus Pyndt Diederichsen; Lærke Marius Kvist; Nicklas Vinter; Grazina Urbonaviciene; Lars Frost (Open Heart)
Aim We examined the diagnostic accuracy of single-lead ECG as assessed by radiographers and 12-lead ECG as assessed by cardiac nurses for the diagnosis of atrial fibrillation (AF).Methods Based on the Danish Cardiovascular Screening Trial, we conducted a population-based, cross-sectional study of 1338 randomly selected Danish men aged 65–74 years with no exclusion criteria. The participants were screened with single-lead ECG during a CT scan assessed by radiographers and 12-lead ECG assessed by cardiac nurses. The diagnostic accuracy was evaluated compared with that produced by a 12-lead ECG assessed by two consenting cardiologists.Results The study identified 68 participants with ongoing AF, of whom 60 had self-reported AF and 8 had AF detected in the screening. Single-lead ECG assessed for AF by radiographers had a sensitivity of 60.3% (95% CI 47.7 to 72.0), specificity of 97.2% (95% CI 96.2 to 98.1), positive predictive value (PPV) of 53.9% (95% CI 42.1 to 65.5) and negative predictive value (NPV) of 97.9% (95% CI 96.9 to 98.6). 12-lead ECG assessed by cardiac nurses had a sensitivity of 97.1% (95% CI 89.8 to 99.6), specificity of 100% (95% CI 99.7 to 100), PPV of 100% (95% CI 94.6 to 100) and NPV of 99.8% (95% CI 99.4 to 100).Conclusions Single-lead ECG assessed by radiographers had a moderate sensitivity and PPV but a very high specificity and NPV. Using radiographers may be acceptable for opportunistic screening, in particular if radiographers are thoroughly trained. Thus, 12-lead ECG assessed by cardiac nurses is a potential diagnostic method for the detection of AF.